Saint Bonaventure A Celebration of the Eighth Centenary of His Birth. - Zamora, Marie Kolbe (The Franciscan Institute, 2021)
"A collection of essays presented at "Frater, Magister, Minister, Episcopus. The Works and Worlds of Bonaventure," a conference held at St. Bonaventure University, commemorating the 800th Centennial of Saint Bonaventure, the Seraphic Doctor"--